Risk factors for hospital readmission of children patients with pneumonia: A systematic review - Christanty, Christanty; Huda, Mega Hasanul; Nurhaeni, Nani; Waluyanti, Fajar Tri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Readmission is an undesirable event influenced by various conditions. While readmission risk factors in pneumonia patients have been widely studied in adults, evidence in children remains limited. Purpose: To identify various risk factors on the rate of hospital readmissions in children with pneumonia. Method: Systematic search following PRISMA guidelines was conducted in PubMed Central, ScienceDirect, Scopus, ProQuest, Wiley, and Google Scholar databases and search engines from inception until September 2025. We used the Joanna Briggs Institute Critical Appraisal Checklist to assess the quality of published studies until they were concluded. Results: Readmission rates in children with pneumonia range from 7% to 16% within 30 to 90 days after hospital discharge. Age risk factors consistently show that younger age (infants to toddlers) significantly increases the risk of childhood pneumonia readmission. Besides that, comorbid conditions and chronic conditions are strong predictors of readmission. Conclusions: Young age and specific chronic comorbid conditions were found to be significant risk factors for hospital readmission among pneumonia patients.